UTILIZING YOUTUBE VIDEO AS MEDIA IN TEACHING STUDENTS’ WORD STRESS PRONUNCIATION - Maspufah Maspufah (Universitas Muhammadiyah Mataram, 2022)
Abstrak: Penelitian ini bertujuan untuk mengetahui apakah pemanfaatan video YouTube dapat meningkatkan kemampuan pelafazan word stress dan mengidentifikasi faktor-faktor yang mempengaruhi peningkatan tersebut. Penelitian ini menggunakan metode penelitian tindakan kelas. Tujuh belas orang mahasiswa dipilih menjadi sample. Data kuantitatif berupa test dan data kualitatif berupa wawancara, observasi, dan catatan lapangan. Data kuantitatif dianalisis dengan menghitung skor tes, sedangkan data kualitatif direduksi, ditampilkan, dan disimpulkan. Hasil analisis menunjukkan pemanfaatan video dari YouTube sebagai media ajar meningkatkan kemampuan mahasiswa dalam melafazkan word stress. Faktor yang mempengaruhi peningkatan tersebut yaitu pemanfaatan video dari YouTube sebagai media ajar. Dengan demikian, dapat disimpulkan bahwa pemanfaatan Video YouTube dapat memberikan hasil yang positif bagi mahasiswa dalam melafazkan word stress.Abstract: The research aimed to identify how good the utilizing of YouTube video as teaching media to improve students’ word stress pronunciation and explain the factors influenced it. The research used action research method. Seventeen students were taken as sample. Quantitative data were from tests, while qualititative data were from interview, observation, and field note. Quantitative data were analysed by scoring test, while qualitative data were reducted, displayed, and concluded. The result showed that the utilizing YouTube Video improved students’ word stress pronunciation. The factors affecting the improvement were the utilizing of YouTube video as teaching media. It can be concluded that the utilizing of YouTube video provided a positive result in students’ word stress pronunciation.